2019
DOI: 10.5296/ijafr.v9i1.14170
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee Characteristics and Audit Report Lag: Evidence From Oman

Abstract: This study examines and provides empirical evidence on the association between audit committee characteristics and audit report lag, by using data from 255 companies listed in the Muscat Securities market from 2013 to 2017. Multivariate analyses show that audit committee size positively associated with audit report lag and audit committee financial expertise reduces audit lag. However, this study does not find evidence that audit committee independence and meetings are associated with audit report lag. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
6
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(93 citation statements)
references
References 41 publications
(108 reference statements)
6
58
6
23
Order By: Relevance
“…Consistent with ARL research, this study controlled for such factors as the internal governance mechanisms monitoring the audit and financial reporting process: the audit committee's (AC) size (ACS), its independence (ACI), its financial expertise (ACFX), and meetings (ACM), and the board size (BOS). Earlier research argued that effective monitoring by these mechanisms reduced audit risks, enabling auditors to reduce their time and effort (e.g., Baatwah et al, 2015;Ghafran & Yasmin, 2018;Raweh, Kamardin, & Malik, 2019a); however, a larger ACS may impede its monitoring function (Bédard & Gendron, 2010), which would demand more audit time and effort (Raweh et al, 2019a). An association was thus expected between ACS and ARL.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with ARL research, this study controlled for such factors as the internal governance mechanisms monitoring the audit and financial reporting process: the audit committee's (AC) size (ACS), its independence (ACI), its financial expertise (ACFX), and meetings (ACM), and the board size (BOS). Earlier research argued that effective monitoring by these mechanisms reduced audit risks, enabling auditors to reduce their time and effort (e.g., Baatwah et al, 2015;Ghafran & Yasmin, 2018;Raweh, Kamardin, & Malik, 2019a); however, a larger ACS may impede its monitoring function (Bédard & Gendron, 2010), which would demand more audit time and effort (Raweh et al, 2019a). An association was thus expected between ACS and ARL.…”
Section: Control Variablesmentioning
confidence: 99%
“…& Bamahros, 2013). For instance, a higher debt ratio, low profits, and weak performance incur greater business risks and irregular reporting, which could increasing both audit time and effort (Abbott et al, 2012;Gros et al, 2017;Raweh et al, 2019a). Finally, industry dummies were also included to control for industry fixed effects.…”
Section: Control Variablesmentioning
confidence: 99%
“…As a result, they found that as much as the audit committees are big with enhancement of independency and with financial experience are likely to be connected with conservatism of earnings in financial institutions in Gulf Cooperation Council (GCC). Raweh, Kamardin and Malik, (2019) study the association between characteristics of audit committee and audit report lag. They show audit committee size has a positive link with audit report and financial expertise of audit committee will lead to reduces audit lag.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Poor performance audit committee leads to weak outputs in the firm's performance and might lead to potential fraud. There are few studies in the literature review towards audit committees features on Oman, (Ahmed, Alabdullah, Thottoli & Maryanti, 2020;Raweh, Kamardin & Malik, 2019;Al-Matari, Al-Dhaafri & Al-Swidi 2019) while there is a need for concentrate on business environment in Oman. With respect to Oman context of the current research, based on late literature, the firms in Oman has faced some challenges and difficulties in different issues in various small, medium and large firms.…”
Section: Introductionmentioning
confidence: 99%
“…‫ةر‬ ‫ة‬ ‫ي‬ ‫تقر‬ ‫ةدار‬ ‫إص‬ ‫ةر‬ ‫ة‬ ‫فت‬ ‫ة‬ ‫ةل‬ ‫ةل‬ ‫دد‬ ‫ةة‬ ‫ة‬ ‫انع‬ ‫الار‬ ‫ةة‬ ‫لنة‬ ‫ةة‬ ‫فعالي‬ ‫ةأثير‬ ‫ة‬ ‫ت‬ ‫ة‬ ‫ةل‬ ‫ةر‬ ‫اتل‬ ‫ةبعض‬ ‫ة‬ ‫ال‬ ‫ةز‬ ‫رد‬ ‫ةا‬ ‫خيةا‬ ‫ةة،‬ ‫انع‬ ‫الار‬ ‫ةة‬ ‫لنة‬ ‫ةة‬ ‫لتعالي‬ ‫ةر‬ ‫ايي‬ ‫إةداد‬ ‫لعل‬ ‫ان‬ ‫انعة‬ ‫الار‬ (Ika and Ghazali ,2012 ;Aljaaidi et al, 2019 ;Hasballah and Ilyas,2019 ;Abdillah et al ,2019 ;Juwita et al ,2020 (Diana,2018;Badawy and Aly,2018;Almuzaiqer et al, 2018;Chukwu and Nwabochi, 2019Aljaaidi et al, 2019Abdillah et al, 2019Shofiyah and Suryani, 2020 ;Yuliusman et al, 2020) ‫ةل‬ ‫بادت‬ ‫ةة‬ ‫تبط‬ ‫الار‬ ‫اا‬ ‫ةر‬ ‫الاتغي‬ ‫ة‬ ‫ةل‬ ‫ةزا‬ ‫رد‬ ‫ةد‬ ‫ا‬ ‫ةرل‬ ‫أل‬ ‫ةاا‬ ‫اس‬ ‫در‬ ‫ةاك‬ ‫لهة‬ ‫انعة‬ ‫الار‬ (Badawy and Aly, 2018;Abdillah et al , 2019 ;Juwita et al, 2020;Pradipta and Zalukhu, 2020 (Diana,2018;Viet et al 2018 Raweh;Chukwu and Nwabochi 2019;Abdillah et al Suryani, 2020 ;Yuliusman et al, 2020) Leventis, 2006;Al-Ajmi,2008 ;Afify,2009 ;Samaha and Khlif ,2017;Ghafran and Yasmin, 2018;Viet et al, 2018;Yuliusman et al , (Al-Ajmi,2008 ;Afify, 2009;Abernathy et al, 2014;Oussii and Taktak ,2018;Viet et al, 2018;Badawy and Aly, 2018;Almuzaiqer et al ,2018;Abdillah et al ,2019Raweh et al , 2019Hasballah and Ilyas, 2019;…”
mentioning
confidence: 99%